Pengaruh Kualitas Pelayanan, Citra Merek Terhadap Keputusan Pembelian Pada E-Commerce Lazada Di Kota Medan - Maya Sari, Roza (Lembaga Riset Ilmiah, 2022)
The high development of internet-specific technology among the public is familiar, bringing influence to society to make a daily necessity. This is used by many companies by opening up online-based business land (E-Commerce). One of the e-commerce that is able to compete today is Lazada. Lazada is here to help the community in buying and selling transactions. This study aims to determine the influence of service quality and brand image on consumers' purchasing decisions on Lazada e-commerce in Medan City. Respondents from this study are people who have transacted and used the Lazada application. This study can be calculated and analyzed multiple linear regression with spss software tool version 24.00. The data collection technique used is a communication technique by spreading questionnaires to obtain data, while in sampling, the technique used is in the form of non-probability sampling. The number of samples taken in this study uses the Lameshow formula, this is because the number of populations is unknown or infinity, so a sample of 100 people was obtained. The results showed that simultaneously the quality of service and brand image influenced consumers' purchasing decisions on Lazada e-commerce in Medan City. Partially, the quality of service has a significant effect on purchasing decisions, and brand image has a positive and significant effect on purchasing decisions on Lazada e-commerce in Medan City.